2005
DOI: 10.1002/chin.200527129
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of 2‐(Substitutedbenzylsulfanyl)benzothiazoles and Their Antimicrobial Activity Screening.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Previously, we reported that benzyl bromide-mediated glycosidation of SBiz-H donor 1 produced 2-benzylsulfanyl-1 H -benzimidazole 39,40 indicating the direct activation of the leaving group via the anomeric sulfur atom. 6 Similarly, when SBiz-H donor 1 was glycosidated in the presence of MeI, disaccharide 4 was obtained along with 2-methylsulfanyl-1 H -benzimidazole 20 (Scheme 5).…”
Section: Resultsmentioning
confidence: 96%
“…Previously, we reported that benzyl bromide-mediated glycosidation of SBiz-H donor 1 produced 2-benzylsulfanyl-1 H -benzimidazole 39,40 indicating the direct activation of the leaving group via the anomeric sulfur atom. 6 Similarly, when SBiz-H donor 1 was glycosidated in the presence of MeI, disaccharide 4 was obtained along with 2-methylsulfanyl-1 H -benzimidazole 20 (Scheme 5).…”
Section: Resultsmentioning
confidence: 96%
“…Among these synthetic strategies, it is worth mentioning the reactions between 2-mercaptobenzoazoles and benzyl halides. These reactions have different issues regarding green approaches, such as heterogeneous catalysts, metallic sodium, or refluxing acetone employment. Other alternatives imply reactions between 2-mercaptobenzoazoles and benzyl alcohols.…”
Section: Introductionmentioning
confidence: 99%